2012
DOI: 10.1128/jvi.07025-11
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Exit: a Novel Control Point in the Accumulation of Antigen-Specific CD8 T Cells in the Influenza A Virus-Infected Lung

Abstract: c Memory/effector T cells efficiently migrate into extralymphoid tissues and sites of infection, providing immunosurveillance and a first line of defense against invading pathogens. Even though it is a potential means to regulate the size, quality, and duration of a tissue infiltrate, T cell egress from infected tissues is poorly understood. Using a mouse model of influenza A virus infection, we found that CD8 effector T cells egressed from the infected lung in a CCR7-dependent manner. In contrast, following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…1). This is in agreement with data demonstrating that upon antigenic stimulation in situ , virus-specific CD8 + T cells decrease their egress from the lung during influenza virus infection (10) and/or develop into long-term T RM cells in the vesicular stomatitis virus-infected brain (31). As T cell entry into tissues is independent of antigen specificity (32), enhancing the retention of antigen-specific T cells by decreased egress from sites of inflammation and infection ensures continued T cell effector functions, while allowing bystander T cells to egress and redistribute.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1). This is in agreement with data demonstrating that upon antigenic stimulation in situ , virus-specific CD8 + T cells decrease their egress from the lung during influenza virus infection (10) and/or develop into long-term T RM cells in the vesicular stomatitis virus-infected brain (31). As T cell entry into tissues is independent of antigen specificity (32), enhancing the retention of antigen-specific T cells by decreased egress from sites of inflammation and infection ensures continued T cell effector functions, while allowing bystander T cells to egress and redistribute.…”
Section: Discussionsupporting
confidence: 92%
“…Lymphocytes were isolated from lymph nodes and spleens by passage through 40 μm cell strainers (BD Biosciences), as described (10). Red blood cells were lysed with 160 mM ammonium chloride and cells washed in RPMI 1640 with 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exiting from tissues requires that CD8 + T cells enter lymphatic vessels that will passively carry them to the draining lymph node and eventually back to the circulation. Like dendritic cells, CD8 + T cells utilize CCR7 to efficiently enter lymphatic vessels before transiting to the draining lymph nodes [79-81]. It has also been reported that S1PR1 also guides CD8 + T cells toward afferent lymphatic vessels [82].…”
Section: Trafficking Of Recently Activated Effector Cd8+ T Cellsmentioning
confidence: 99%
“…124,125 During influenza virus infection, the exit of effector CD8 T cells from the lungs is facilitated by the CCR7 ligand, CCL21, which is expressed in lymphatic endothelial cells during infection. 126 Once CCR7 is downregulated, the rate of T-cell migration from the lung tissues to the mediastinal LN diminishes. In contrast, forced expression of CCR7 results in more rapid exit of effector T cells from the lung, 122 whereas in another model CCR7 deficiency prevents tissue-resident lymphocytes from leaving the skin.…”
Section: Retention and Exit Of Pathogen-specific T Cells From The Mucmentioning
confidence: 99%